The efficacy of pericapsular nerve group block for postoperative analgesia in patients undergoing hip surgery: A systematic review and meta-analysis of randomized controlled trials - Yu, Liang; Shen, Xiaojuan; Liu, He (Frontiers in Medicine, 2023)
Background: Pericapsular nerve group (PENG) block has been increasingly applied in patients for postoperative analgesia. This meta-analysis aimed to determine the efficacy of PENG block in adults undergoing hip surgery compares with other types of nerve block. Methods: A total of 497 academic articles were identified after systematic search of the PubMed, Embase, Web of science, and Cochrane Library databases up to August 25, 2022. Results: Numerous electronic databases were searched and finally 9 studies were identified. There was no significant difference in the postoperative 24 hours morphine consumption (mean difference [MD]: -2.57, 95% confidence interval [CI]: [-5.42, 0.27], P = 0.08) and the time first to request rescue analgesia (MD: 1.79, 95% CI: [-1.06, 4.64], P = 0.22) between PENG block and the control groups. The PENG block did not reveal a significant difference in 6 hours (MD: -0.17, 95% CI: [-0.92, 0.57], P = 0.65), (MD: -0.69, 95% CI: [-1.58, 0.21], P = 0.13) and 24 hours (MD: -0.25, 95% CI: [-1.54, 1.05], P = 0.71), (MD: 0.05, 95% CI: [-0.84, 0.93], P = 0.91) static and dynamic pain score compare with other nerve block methods. Moreover, the two groups have the similar risk of postoperative nausea and vomiting (PONV) (odds ratio [OR]: 1.29, 95% CI = 0.53-3.10, P = 0.57). Conclusion: This review showed that there was no statistically significant difference in postoperative analgesic effect between PENG block and the other kinds of nerve block. PENG block can be used as an alternative for multimodal analgesia in hip surgery.